Ceramic vs polymeric membrane implementation for potable water treatment - Jarvis, Peter; Carra, Irene; Jafari, M.; Judd, Simon J. (Elsevier, 2022)
The continued technological developments and decreased purchase costs of ceramic membranes have seen increased recent interest in the technology as an alternative to the more widely used polymeric membranes. This paper assesses the relative technical, practical and economic merits of the two membrane materials in the context of potable water production from surface water sources. The work focuses on phenomena of direct technoeconomic significance, namely cleaning efficacy (manifested as permeability recovery), membrane integrity and incurred labour effort. Topics reviewed thus comprise: (a) practical comparison of the two technologies challenged with the same feedwater, (b) comparative technoeconomic analyses, (c) membrane integrity studies of polymeric membranes - incorporating aged samples extracted from operating installations, (d) sludging incidents, and (e) pilot and full-scale data. Available relevant data reveal: (a) bench-scale comparative tests do not indicate a consistent significant difference in the net permeability between the two membranes; (b) polymeric membranes are subject to a decline in both mechanical strength and permeability from the loss of the hydrophilic agent over a period of years from the action of hypochlorite used for cleaning; (c) the decreased mechanical strength with age of polymeric membranes increases the manual repair requirement and shortens membrane life, respectively impacting on labour and membrane replacement costs where the latter is also determined by the permeability; (d) the chemical and mechanical robustness of ceramic membranes permits more aggressive chemical cleaning, which then affects the chemicals consumption cost; and (e) anecdotal evidence suggests that polymeric membranes challenged with pre-coagulated surface waters may be subject to sludging, the agglomeration of solids in the membrane channels, which may also be age-related. Notwithstanding the above, data from published comparative technoeconomic studies indicate a linear relationship between the overall cost benefit and the membrane module cost ratio mitigated by the relative membrane life and operating flux.
Keywords: Ceramic membranes; Polymeric membranes; Integrity; Cost; Life; Flux